Actualization of Qur'anic Values and Living Values in Strengthening The Character of MTsN 1 Sukamara Students in the Society 5.0 Era - Sabilah Labibah; Surawan Surawan (Faculty of Teacher Training and Education, Palangka Raya University, Central Kalimantan, Indonesia. Pos Code 73112, 2025)
Technological developments in the Society 5.0 era not only bring convenience but also raise moral and character issues among students, requiring an educational model capable of addressing these challenges in a broader context. This study aims to analyze how Qur'anic values and Living Values Education (LVE) are integrated in strengthening students' character education and to test its effectiveness as a model for Islamic character building. Using a descriptive quantitative method, the research was conducted through a survey of 300 students in grades VII, VIII, and IX at MTsN 1 Sukamara, Central Kalimantan, with a closed questionnaire containing 15 statements covering the variables of understanding, application, and impact of Qur'anic values and LVE. Data analysis was carried out to see the response trends and the relationship between variables. The results showed that students had a good level of understanding of the importance of Qur'anic-based character education (65.8%), teachers consistently linked learning to Qur'anic values (50.7%), and regular religious activities contributed significantly to character building (60.7%). Although social media influences behavior (50.3%), students still try to filter digital content according to Islamic teachings (55%). These findings indicate that the integration of Qur'anic values and LVE effectively strengthens students' religious, social, and digital character. The implications of this study confirm that this integrative approach can be used as a model for character education policies and practices in Islamic educational institutions. In conclusion, the Qur'anic-LVE integration model is relevant for application in the Society 5.0 era and is recommended for further development in subsequent studies. Perkembangan teknologi pada era Society 5.0 tidak hanya membawa kemudahan, tetapi juga memunculkan persoalan moral dan karakter pada peserta didik, sehingga dibutuhkan model pendidikan yang mampu menjawab tantangan tersebut dalam konteks yang lebih luas. Penelitian ini bertujuan menganalisis bagaimana nilai-nilai Qur’ani dan Living Values Education (LVE) diintegrasikan dalam penguatan pendidikan karakter siswa serta menguji efektivitasnya sebagai model pembinaan karakter Islami. Menggunakan metode kuantitatif deskriptif, penelitian dilakukan melalui survei terhadap 300 siswa kelas VII, VIII, dan IX MTsN 1 Sukamara, Kalimantan Tengah, dengan angket tertutup berisi 15 pernyataan yang mencakup variabel pemahaman, penerapan, dan dampak nilai Qur’ani serta Living Values Education (LVE). Analisis data dilakukan untuk melihat kecenderungan respons serta hubungan antarvariabel. Hasil penelitian menunjukkan bahwa siswa memiliki tingkat pemahaman yang baik terhadap pentingnya pendidikan karakter berbasis Qur’ani (65,8%), guru konsisten mengaitkan pembelajaran dengan nilai-nilai Al-Qur’an (50,7%), dan kegiatan keagamaan rutin berkontribusi signifikan terhadap pembentukan akhlak (60,7%). Meskipun media sosial berpengaruh terhadap perilaku (50,3%), siswa tetap berupaya menyaring konten digital sesuai ajaran Islam (55%). Temuan ini menunjukkan bahwa integrasi nilai Qur’ani dan LVE efektif memperkuat karakter religius, sosial, dan digital siswa. Implikasi penelitian ini menegaskan bahwa pendekatan integratif tersebut dapat dijadikan model kebijakan dan praktik pendidikan karakter di lembaga pendidikan Islam. Kesimpulannya, model integrasi Qur’ani–LVE relevan diterapkan di era Society 5.0 dan direkomendasikan untuk dikembangkan dalam penelitian lanjutan